Respuesta :

Answer:

Did you even look at it? g(x)=2x

Step-by-step explanation:

2x-6=2(x-3), or 2(x).

The required formula of g(x) is 2x.

We have to determine, formula for g(x) if it is known that g(x-3) = 2x-6.

To obtain the formula of g(x) follow all the steps given below.

According to the question,

The formula of g(x),

g(x - 3) = 2x - 6

  • Step1;  To find the expression (x - 3) = y in the g(x - 3)

          Then,

           [tex]g(x - 3) = 2x - 6 = 2x - 2\times 3[/tex]

  • Step2; Taking the common factor 2,

            [tex]=2x -2\times 3\\\\ = 2(x - 3)\\\\\ let \ x-3 = y\\\\ = 2y[/tex]

           Then,

            [tex]g( x - 3) = g(y) = 2y[/tex]

         

  • Step3;  Replace x by y,

       Then,

       g(x) = 2x

Hence, The required formula of g(x) is 2x.

To know more about Function click the link given below.

https://brainly.com/question/20714290

ACCESS MORE